Balancing National Sovereignty and the Efficiency of Cross-Border Asset Enforcement: Toward an ASEAN Framework for the Recognition and Enforcement of Foreign Court Judgments - Geraldine Eka Al-Fara Airanun (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the institutional conflict between state sovereignty and transnational enforcement efficiency within the Association of Southeast Asian Nations, focusing specifically on the conservative legal frameworks of Indonesia and Thailand. Utilizing a non-empirical doctrinal legal method and macro-comparative analysis, the investigation deconstructs the systemic barriers generated by traditional territorial enforcement paradigms that refuse to recognize foreign judicial decrees directly. The current domestic requirements for comprehensive re-litigation multiply corporate transaction costs, cause prolonged procedural delays, and undermine cross-border asset recovery mechanisms within the regional market. To resolve this regional enforcement gap, this study designs a normatively viable regional blueprint titled the ASEAN Framework for the Recognition and Enforcement of Foreign Judgments. By adapting global circulation standards from the Hague Judgments Convention 2019 and the Brussels I Recast Regulation, the proposed model introduces a streamlined registration tracking mechanism balanced with a restrictive grounds for refusal matrix. This integrated architectural framework successfully eliminates structural legal duplication, secures cross-border data privacy, and combats transnational financial crimes while preserving the foundational judicial autonomy of individual member nations.